QM/MM calculations reveal the different nature of the interaction of two carborane-based sulfamide inhibitors of human carbonic anhydrase II - Pecina, Adam; Lepšík, Martin; Řezáč, Jan; Brynda, Jiří; Mader, Pavel; Řezáčová, Pavlína; Hobza, Pavel; Fanfrlík, Jindřich (The journal of physical chemistry. B, 2013)
The crystal structures of two novel carborane-sulfamide inhibitors in the complex with human carbonic anhydrase II (hCAII) have been studied using QM/MM calculations. Even though both complexes possess the strongly interacting sulfamide···zinc ion motif, the calculations have revealed the different nature of binding of the carborane parts of the inhibitors. The neutral closo-carborane cage was bound to hCAII mainly via dispersion interactions and formed only very weak dihydrogen bonds. On the contrary, the monoanionic nido cage interacted with the protein mainly via electrostatic interactions. It formed short and strong dihydrogen bonds (stabilization of up to 4.2 kcal/mol; H···H distances of 1.7 Å) with the polar hydrogen of protein NH2 groups. This type of binding is unique among all of the classical organic and inorganic inhibitors of hCAII. Virtual glycine scanning allowed us to identify the amino-acid side chains, which made important contributions to ligand-binding energies. In summary, using QM/MM calculations, we have provided a detailed understanding of the differences between the interactions of two carborane sulfamides, identified the amino acids of hCAII with which they interact, and thus paved the way for the computer-aided rational design of selective boron-cluster-containing hCAII inhibitors.
Keywords: inhibitory karboanhydras; Models, Molecular; borany; Catalytic Domain; Carbonic Anhydrase II; Quantum Theory; krystalografie rentgenová; Boranes; karboanhydrasa II; Carbonic Anhydrase Inhibitors; Humans; Amides; lidé; Crystallography, X-Ray; katalytická doména; amidy; molekulární modely; kvantová teorie